TESLA - The Superconducting Electron Positron Linear Collider with an Integrated X-Ray Laser Laboratory. Technical Design Report : Part III - Physics at an e+e- Linear Collider - Dova, María Teresa (2001)
The Standard Model of particle physics was built up through decades of intensive dialogue between theory and experiments at both hadron and electron machines. It has become increasingly coherent as experimental analyses have established the basic physical concepts. Leptons and quarks were discovered as the fundamental constituents of matter. The photon, the W and Z bosons, and the gluons were identified as the carriers of the electromagnetic, weak and strong forces. Electromagnetic and weak forces have been unified within the electroweak gauge field theory. The QCD gauge field theory has been confirmed as the theory of strong interactions.